Percutaneous lordoplasty for the treatment of severe osteoporotic vertebral compression fractures with kyphosis - Song, Tengfei; Sun, Fan; Liu, Shu; Ye, Tianwen (Frontiers in Neurology, 2023)
Objective: To explore the safety and effectiveness of percutaneous lordoplasty (PLP) in the treatment of severe osteoporotic vertebral compression fracture (OVCF). Methods: Included in this prospective study were 51 patients with single-segment acute severe OVCF who were treated with PLP in our institution from July 2016 to October 2019. Patients’ back pain and quality of life were assessed by VAS and SF-36 scores. Lateral X-ray radiography of the spine was performed to measure the vertebral height, vertebral kyphotic angle and segmental kyphotic angle, and evaluate the outcome of fracture reduction and kyphotic correction. Intra-and postoperative complications were recorded. Results: Of the 51 included patients, 47 patients were followed up for 12 months. The VAS score decreased from preoperative 7.33±1.92 to postoperative 1.76±0.85 at 12th month (p < 0.05), and the SF-36 score increased from preoperative 79.50±9.22 to postoperative 136.94±6.39 at 12th month (p < 0.05). During the one-year follow-up period, the anterior height of the vertebral body increased significantly from preoperative 10.49±1.93mm to 19.33±1.86mm (P < 0.05); the posterior height of the vertebral body increased insignificantly from preoperative 22.23±2.36mm to 23.05±1.86mm (P >0.05); the vertebral kyphotic angle decreased significantly from preoperative 18.33°±11.49° to 8.73°±1.21° (P < 0.05); and the segmental kyphotic angle decreased significantly from preoperative 24.48°±4.64° to 11.70°±1.34°(P < 0.05). During the one-year follow-up period, there was no significant difference found in the radiologic parameters，VAS and SF-36 scores between 1st day and 12th month post-operation (P>0.05). No nerve damage occurred in any case. Intraoperative cement leakage occurred in six cases, and fracture of the adjacent vertebral body occurred in one case. Conclusion: PLP can well reduce the risk of fracture and achieve good kyphotic correction, and may prove to be a safe, cost-effective and minimally invasive alternative option for the treatment of severe OVCF with kyphotic deformity.